Assessment of Attitude tetep, antep, mantep in the Teaching: Ki Hadjar Dewantara Perspective - Rahayu Retnaningsih; Samsi Haryanto; Awang Damar; Puspa Eka Ayu Febriana (STAI Hubbulwathan Duri, 2023)
Ki Hadjar Dewantara's tetep, antep, and mantep attitude assessment is the focus of this research. Descriptive qualitative research is conducted in the form of a literature review that objectively examines the process of developing Ki Hajar Dewantara's attitude evaluation instrument (tetep, antep, mantep). The purpose of the descriptive method is to provide sufficient background information for further analysis and conclusion drawing. Analysis and recording of studies serve as the basis for the data collection. Books and articles are gathered for research at libraries. Data collected from documentation and field data poured in a thorough and detailed report description form the basis of the interactive model analysis. A summary is created at the outset of data gathering, which is when data reduction occurs. The next step is trimming the data and field reports to the essentials, highlighting the most relevant information, and looking for recurring themes or patterns. Data is reduced in complexity by selection, classification, and abstraction. Data visualisation aids researchers in gaining a better understanding of the whole or of specific subsets of their data. Fourth, by categorising the data, researchers are able to draw meaningful conclusions. The study's findings indicated that the sensitivity index value was the most reliable predictor of Ki Hadjar Dewantara's tetep, antep, and mantep attitudes towards his students' academic progress. Contextual learning models that incorporate local expertise can be used to refine evaluations of Ki Hadjar Dewantara's tetep, antep, mantep attitude.